A comparative field evaluation of six medicine quality screening devices in Laos - Caillet, C; Vickers, S; Zambrzycki, S; Fernández, FM; Vidhamaly, V; Boutsamay, K; Boupha, P; Peerawaranun, P; Mukaka, M; Newton, PN (Public Library of Science, 2021)
Background Medicine quality screening devices hold great promise for post-market surveillance (PMS). However, there is little independent evidence on their field utility and usability to inform policy decisions. This pilot study in the Lao PDR tested six devices’ utility and usability in detecting substandard and falsified (SF) medicines.